IS STAINLESS STEEL REALLY “STAINLESS”? - Porteous, Joan (Operating Room Nurses Association of Canada Journal, 2011)
Initial purchase and replacement costs for surgical instrumentation are significant components in today’s operating room budgets. OR staff and medical device reprocessing personnel work together as a team to ensure effective management of this valuable commodity. The purpose of this article is to discuss the composition of stainless steel surgical instruments, to identify processes to minimize damage to instruments caused by staining, corrosion, and pitting, and to utilize that information to describe effective measures to manage instrumentation in both the OR and reprocessing areas. A significant portion of OR budgets is dedicated to purchasing surgical instruments. In order to get value for these health care dollars, we make efforts to prolong the life of these instruments by conscientious intraoperative management and scientific reprocessing techniques. The purpose of this article is to discuss the composition of stainless steel surgical instruments and to identify processes to minimize damage to instruments caused by staining, corrosion and pitting. What are some effective strategies that perioperative nurses and medical device reprocessing personnel can employ to help to prolong the life of surgical instruments?